Pseudo-homogeneous kinetic model for esterification of acetic acid with propanol isomers over dodecatungstophosphoric acid supported on montmorillonite k10 - Gurav, Hanumant R.; Nandiwale, Kakasaheb Y.; Bokade, Vijay V. (Journal of Physical Organic Chemistry, 2014)
Esterification of acetic acid with propanol isomers such as isopropanol and naEuropropanol was carried out over dodecatungstophosphoric acid (DTPA), dodecamolybdophosphoric acid ammonium salt hydrate, and sodium tungstate hydrated purified supported on montmorillonite K10, which were characterized by powder XaEuroray diffraction, BrunaueraEuro'EmmettaEuro'Teller, and temperature programmed ammonia desorption. A pseudoaEurohomogeneous (PaEuroH) kinetic model was established for esterification of acetic acid with propanol isomers over DTPA supported on montmorillonite K10. Effects of various parameters such as reaction time, speed of agitation, particle size, temperature, percent catalyst loading, molar ratio and mixture of propanol isomer were investigated in detail. The 20% (w/w) DTPA/K10 was found to be an optimum solid catalyst with 82% naEuropropanol and 53% isopropanol conversion with 100% selectivity toward propyl acetate. The 20% (w/w) DTPA/K10 catalyst was found to be reusable for three cycles. The reaction follows secondaEuroorder kinetics with activation energies of 25.53aEuro?kJaEuro?mol(a?'1) and 28.15aEuro?kJaEuro?mol(a?'1) for isopropanol and naEuropropanol, respectively. PseudoaEurohomogeneous kinetic model fitted with R-2 value of trend line 0.999. This implies that esterification reaction is kinetically controlled owing to high activation energy. Copyright a (c) 2013 John Wiley & Sons, Ltd.
Keywords: Acetic acid; dodecatungstophosphoric acid; Esterification; kinetic model; montmorillonite K10